Eosinophilic annular erythema is clinically characterized by central pigmentation reflecting basal melanosis: a clinicopathological study of 10 cases. (21st June 2017) - Nakazato, S.; Fujita, Y.; Shinkuma, S.; Nomura, T.; Shimizu, H.
Abstract: Background: Eosinophilic annular erythema (EAE) has been proposed as a clinical entity to describe annular skin lesions associated with tissue eosinophilia. However, systematic investigations on the histopathology of EAE have not been performed, and useful histopathological findings for diagnosis of EAE remain unknown. Objective: The aim of this study was to investigate the clinicopathological features of EAE. Methods: We retrospectively studied 10 patients at our hospital during a 5‐year span who clinically showed annular or figurate lesions and histopathologically exhibited eosinophilic infiltration in the dermis. Results: Nine of the 10 cases had annular lesions with pigmentation on the interior side. Blood eosinophilia was found in only one patient. Histopathologically, basal melanosis was observed in nine cases. Infiltration of eosinophils was confined to the dermis in nine cases. Patients treated with systemic corticosteroid tended to show less recurrence than those treated with topical corticosteroid. Limitations: The main limitation of our study is the small number of patients. Conclusion: Skin biopsy should be performed when EAE is suspected, even in cases without blood eosinophilia. Basal melanosis and tissue eosinophilia confined to the dermis suggest the diagnosis of EAE. We recommend topical corticosteroids as the initial treatment for EAE.